2023
DOI: 10.20944/preprints202306.0926.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Physicochemical Characteristics, Selected Lipid Content and Protein Bioactive Compounds of Lamb Meat Depending on Aging Time and Muscle Type

Aurelia Radzik-Rant,
Witold Rant,
Marcin Świątek
et al.

Abstract: Many factors affect the quality of red meat. The aim of the study, carried out on 44 Polish Merino lambs, was analysis of physicochemical traits (pH, meat color, expressed juice, content of moisture, protein, fat, total collagen and fatty acid ) and content of carnosine, taurine, L-carnitine on fresh and meat aged for 7 and 14 d in the longissimus lumborum (LL) and gluteus medius (GM) muscles., Higher (p<0.05) redness value (a*), lower yellowness (b*) were recorded in meat after of aging in gluteus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
2
0
0
Order By: Relevance
“…The reason for this could be interpreted as the proportionally higher fat content in the meat composition of Korean Hanwoo cattle. The moisture content in lamb meat was similar (Junkuszew et al, 2020;Khal-Azzawi and Albashr, 2022;Lima et al, 2022), lower (Mioč et al, 2007;Meng et al, 2023;Radzik-Rant et al, 2023) or higher than (Romero-Bernal et al, 2017;Liang et al, 2023) other reported researches. The moisture content reported for chicken meat was similar (Silva Frasao et al, 2021;Xu et al, 2021) to the rates found in the study.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The reason for this could be interpreted as the proportionally higher fat content in the meat composition of Korean Hanwoo cattle. The moisture content in lamb meat was similar (Junkuszew et al, 2020;Khal-Azzawi and Albashr, 2022;Lima et al, 2022), lower (Mioč et al, 2007;Meng et al, 2023;Radzik-Rant et al, 2023) or higher than (Romero-Bernal et al, 2017;Liang et al, 2023) other reported researches. The moisture content reported for chicken meat was similar (Silva Frasao et al, 2021;Xu et al, 2021) to the rates found in the study.…”
Section: Resultssupporting
confidence: 73%
“…The protein values found for cattle in the study were similar to some of the values found in the researches (Hamed Hammad Mohammed et al, 2020;Pouzo et al, 2023;Santana et al, 2023), higher than some (Salim et al, 2023) and lower than some (Oliveira et al, 2021;Ngom et al, 2022). While the values reported for sheep were in agreement with (Costa et al, 2009;Romero-Bernal et al, 2017;Radzik-rant et al, 2023) or higher than literature reports and findings (Mioč et al, 2007;Lima et al, 2022;Latoch et al, 2023;Lunesu et al, 2023;Uushona et al, 2023). The rates found for chicken meat were higher than the reported values Xu et al, 2021;Sugiharto et al, 2022;Weng et al, 2022;Fathi et al, 2023).…”
Section: Figure 2 Ash Content Of Meat Samples Obtained From Different...supporting
confidence: 86%